Development and Validation of UV- Spectrophotometric Method for estimation of Vancomycin Hydrochloride - Pande, Saikat; Parikh, Jolly R (Journal of Drug Delivery and Therapeutics, 2019)
UV-spectrophotometry refers to absorption spectroscopy or reflectance spectroscopy in the ultraviolet-visible spectral region. This method of analysis is gaining importance as it is rapid, simple, precise, less time consuming and highly accurate. The objective of the present investigation was to develop an accurate, rapid and robust method for determination of Vancomycin hydrochloride in pharmaceutical preparations by using UV spectrophotometric method. Vancomycin hydrochloride shows maximum absorbance at a wavelength of 281 nm, which is used for this study. The method provides a linear response from a quantitation range of 20 µg/ml to 100 µg/ml in phosphate buffer pH 6.8 with regression equation y = 0.0038x + 0.0045 and r2 0.9994. Interday precision and accuracy was found to be below 0.2 and above 99.00% respectively for the developed method. Thus the developed method may be suitably applied for regular quality control of Vancomycin hydrochloride in bulk and pharmaceutical preparations. Keywords: Vancomycin hydrochloride, spectroscopic method, validation.